Social Upgrading as Market Fantasy: The Limits of Global Value Chain Integration. Issue 2 (July 2019) - Fridell, Gavin; Walker, Chris
Confronted with mixed evidence linking economic upgrading in global value chains to improved social outcomes, proponents have called for a new emphasis on "social upgrading" to promote better employment, gender equality, and poverty reduction. Originally focused on a central role for states, unions, and social movements, the discourse on social upgrading has shifted, emphasizing the benefits of corporate social responsibility and global markets. Drawing on political economic, critical theory, and psychoanalytic paradigms, we explore the politics of this shift and argue that social upgrading is gradually being deployed as a neoliberal market fantasy, designed not to challenge the limits of market integration, but to obscure and deny them. The strength of the social upgrading discourse emerges less from its pretense toward objective, data-driven analysis, than its effectiveness as an ideological fantasy in meeting the contradictory, non-rational desires of experts and non-experts.